Be Here Now: Immanent Utopias and Permanent Revolution - Matt York (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
ABSTRACT: With the breathtaking proliferation of polycrises unfolding around us, the central problem this article takes as its starting point is the nature of our current political utopias—that they are transcendent rather than grounded. Or, to put it another way, rather than being here-and-now, they are nowhere, situated in an ever-receding future or past, or otherwise in an alternate reality altogether. They are impossible. This article’s argument is that, if we are to move beyond our current states of bewilderment, disorientation, and denial, we must set new political trajectories which aim not at our current utopias (which are not-now and nowhere) but toward those that are both now and here, and therefore possible. Drawing on classical and contemporary anarchist theory, and from participants of the ongoing Deep Commons collective visioning project, the perceived antinomy of revolutionary and evolutionary theories of political and social change will be questioned, and the anarchist concept of permanent revolution—an ongoing process without end—will be explored as an alternative model for radical social transformation. The temporal gap between current struggles and imagined futures will be problematized, prefigurative praxes critiqued, and a politics of immanence explored as a remedy. Finally, this article considers reframing the sequencing of means and ends from a linear to a non-linear temporal form. Thus, rather than prefiguring a path which leads to a particular goal, we reframe the path as the goal.